Pathological responses to intratracheally instilled polycyclic aromatic hydrocarbons and effects of curcumin towards these responses in sprague dawley rats - Karim, Abdulkarim Jafar (2010)
Increasing attention is diverted to air pollution since its impact is extremely diversified. One of the ubiquitous environmental pollutants is the polycyclic aromatic hydrocarbon (PAH). The aim of this study was to assess several aspects of air pollution on bodily function and morphology. This study was designed based on the occurrence of the PAHs in the Malaysian 1997 haze episode using four selected PAHs. These were benzo[a]pyrene (BaP), benzo[a]anthracene (BaA), benzo[e]pyrene (BeP) and phenanthrene (Phen). These PAHs were instilled individually by intratracheal (IT) route to male rats and either singly or in combination for a period of one month. Blood was taken at days 0.5, 3, 7, 21, 60 and 180. The same timeline was used to euthanize the rats. Bronchoalveolar lavage (BAL) was conducted and lung sampling was done for H&E, transmission electron microscope (TEM) and TUNEL assay to study apoptosis. Blood and BAL were used to study the hepatic enzymes, oxidative and immune status of the rats. Curcumin was given via diet along with BaP and PAHs combination to test its ability to ameliorate the PAHs injuries. There was a close relationship between the blood and BAL fluid with histopathological findings. Out of the four PAHs, only BaP produced neoplastic growth in different sites of the body. Microscopic lesions revealed the ability of BaP, and to a lesser extent BaA, to induce hyperplasia, dysplasia and atypia which are pivotal steps into carcinogenesis while Phen resulted in pulmonary fibrosis. The effect BeP and the PAHs combination (Comb) were reversible with no longer than 21 days PI. The TUNEL assay was effective in detecting apoptosis with high percentages in the BeP and Comb groups explaining the reversible trends in these groups. Carcinogenesis, pulmonary fibrosis and the initiators for lung carcinogenesis is suggested by this study to be oxidative stress dependent. The severity of mitochondrial corruption was proven by TEM in this study to be PAH-dependent. This resulted in significant imbalance in the phase I metabolic enzymes, superoxide dismutase (SOD) and other oxidative enzymes [glutathione peroxidase (GSHpx), glutathione reductase (GR)], which maintain normal levels of reactive oxygen species (ROS). Theoretically, this plays a great part in triggering apoptosis. Practically, ROS was measured by malondialdehyde (MDA) level and the ratio between reduced to oxidized glutathion (GSH:GSSG).However, owing to the lack of specifity, none of the oxidative enzymes ascertain the exposures to PAHs. Anyway, the MDA and GSH:GSSG are proven by this study to be beneficial in detecting PAH deteriorations. Following acute response (day 0.5 PI) to PAH exposure, all PAHs were able to produce significant elevations in BALF immunoglobulins (Ig). Chronic responses (day 180 PI) showed a significant drop in Ig in the Phen group due to cytotoxicity marked by the alveolar macrophage activity test. In contrast, IgG in the BaP group was striking due to autoimmune antibodies produced in carcinogenesis. Dietary supplementation of curcumin showed significant improvement in lung milieu and the oxidant/antioxidant status. It up-regulates the blood oxidative enzymes. Furthermore, curcumin increases the rate of apoptosis, a pathway to get rid of defective cells. In conclusion, lung tissues have varied responses to PAHs species. The BaP can produce tumorogenesis not only confined to the lung. Combination of PAHs has a mild effect than some individual PAH did. Curcumin has a potent effect in alleviating these deleterious effects.